Patterns of positivity: Positive affect trajectories among infants of mothers with a history of depression. (21st October 2019) - Davis, Molly; Goodman, Sherryl H.; Lavner, Justin A.; Maier, Meeka S.; Stowe, Zachary N.; Newport, D. Jeffrey; Knight, Bettina
Abstract: This study examined positive affect (PA) trajectories over the first year of life among infants of mothers with a history of depression ( N = 191) as well as predictors (i.e., maternal prenatal and postpartum depression symptoms, maternal parenting behaviors) of those trajectories. Infant PA was observed in play and feeding tasks during laboratory visits at 3, 6, and 12 months of age; parenting behaviors were observed at 3 months. Mothers completed questionnaires regarding their symptoms of depression throughout the prenatal period and during the first 3 months postpartum. Growth curve analyses indicated that infant PA increased across time, and this finding replicated across both the play and feeding tasks, though increases slowed over time. Neither maternal prenatal nor postpartum depression symptoms predicted infants' PA trajectories, but mothers' PA, positive parenting, and disengaged parenting were associated with infant PA during the play task. Our finding that infant PA increased over the first year postpartum suggests PA trajectories among infants of mothers with a history of depression may be indices of resilience, despite risks associated with their mothers' history of depression. Furthermore, this study highlights parenting behaviors that may be important targets of prevention and early intervention efforts to bolster infant PA.